What Are We Learning from Business Training and Entrepreneurship Evaluations around the Developing World? - McKenzie, David (Oxford University Press on behalf of the World Bank, 2015)
Business training programs are a popular policy option to improve the performance of enterprises around the world, and the number of rigorous impact evaluations of these programs is growing. A critical review reveals that many evaluations suffer from small sample sizes, measure impacts only within a year of training, and experience problems with survey attrition and measurement that limit the conclusions one can draw. Over these short time horizons, there are relatively modest effects of training on the survivorship of existing firms. However, there is stronger evidence that training programs help prospective owners launch new businesses more quickly. Most studies find that existing firm owners implement some of the practices taught in training, but the magnitudes of the improvement to practices is often modest. Few studies find significant impacts on profits or sales, although some studies with greater statistical power have done so. There is little evidence to guide policymakers regarding whether any identified effects are due to trained firms drawing sales from competing businesses rather than through productivity improvements or to guide the development of the provision of training at market prices. We conclude by summarizing some directions and key questions for future studies.